2003
DOI: 10.1016/j.otohns.2003.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Otosclerosis in Elderly Patients

Abstract: Stapes surgery is an effective procedure in elderly patients with otosclerosis to avoid hearing aid use or to facilitate hearing aid fitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 9 publications
1
7
0
12
Order By: Relevance
“…Stapedectomy in seniors is controversial. It is indicated to avoid the use of a hearing aid or to facilitate hearing aid fitting, when the association of otosclerosis and presbyacusis makes hearing aid provision unsatisfactory (54). Whereas some authors have reported lower success rates in the elderly than in younger patients (55,56), others, however, think that old age does not preclude stapes surgery (53,54,57Y60).…”
Section: Stapes Surgery In Childrenmentioning
confidence: 99%
“…Stapedectomy in seniors is controversial. It is indicated to avoid the use of a hearing aid or to facilitate hearing aid fitting, when the association of otosclerosis and presbyacusis makes hearing aid provision unsatisfactory (54). Whereas some authors have reported lower success rates in the elderly than in younger patients (55,56), others, however, think that old age does not preclude stapes surgery (53,54,57Y60).…”
Section: Stapes Surgery In Childrenmentioning
confidence: 99%
“…Prosthesis dislocation, migration out of the oval window fenestra, and complete incus erosion were the most common causes for failure in this series. Several studies have commented on the variable of patient age at the time of stapes surgery [5,6]. Stapedectomy in seniors is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Efekty uruchomienia strzemiączka nie są trwałe. Chirurgiczne usunięcie suprastruktury strzemiączka uznawane jest w literaturze za najskuteczniejszą metodę leczenia otosklerozy u osób w każdym wieku [1,3,4,10].…”
Section: Wstępunclassified
“…Według licznych doniesień naukowych otoskleroza dużo częściej występuje u kobiet niż u mężczyzn [10][11][12][13][14][15][16][17][18][19]. Ta tendencja jest widoczna także w grupie osób starszych (po 60. roku życia).…”
Section: Wyniki Dane Sojodemograficzneunclassified
See 1 more Smart Citation